Resonance in the Age of Remote Work: Organisational Strategies for Adapting to Technical Acceleration - Ostroff,Aaron; Mitchell,Carter (2025)
Our thesis investigates the effects that strategies aligned with resonance theory have on organisations when they are used to adapt to technical acceleration. To do so, we use retrospective case studies and qualitative interviews to understand how organisations adapted to the rapid implementation of remote work during the COVID-19 pandemic in the United States. We analyse internal methods of adaptation through a tripart theoretical lens: we use social acceleration theory to contextualise the events within the case studies, and perform separate analyses of these events using resonance theory and the Job Demands–Resources (JD-R) model. Our comparison of these analyses revealed an alignment between the JD-R model’s findings on the effects well-executed technical adaptation has on employee wellness and the process and outcomes of adaptive transformation presented by resonance theory. These results suggest that strategies aligned with resonance theory can have positive effects on employee well-being as well as organisational culture and resilience when used to adapt to technical acceleration. Accordingly, our research suggests that resonance theory may be a useful framework for organisational management, especially for navigating change in an era of accelerating innovation and demands.
Keywords: Social acceleration; technical acceleration; resonance; adaptation; strategy; job demands; job resources; digitization; employee well-being